Different Risk of Common Gastrointestinal Disease Between Groups Undergoing Hemodialysis or Peritoneal Dialysis or With Non-End Stage Renal Disease. Issue 36 (September 2015) - Lee, Yi-Che; Hung, Shih-Yuan; Wang, Hsi-Hao; Wang, Hao-Kuang; Lin, Chi-Wei; Chang, Min-Yu; Ho, Li-Chun; Chen, Yi-Ting; Wu, Ching-Fang; Chen, Ho-Ching; Wang, Wei-Ming; Sung, Junne-Ming; et al.
<x xml:space="preserve">Abstract</x> Abstract Peritoneal dialysis (PD) is one type of renal replacement therapy, but potential peritoneal damage and gastrointestinal (GI) tract adverse effects during long-term exposure to bio-incompatible dialysate remain a concern. Although GI disease frequently occurs in dialysis patients, whether the risk of GI diseases differs among PD and hemodialysis (HD) or non-uremic groups is still uncertain. In this retrospective cohort study, data were obtained from the National Health Insurance Research Database, which includes almost all dialysis patients in Taiwan. Between 2000 and 2009, a total of 1791 PD and 8955 HD incident patients were enrolled and matched for age and sex or for propensity score. In addition, a comparison cohort of 8955 non-uremic patients was also selected. Individuals were monitored for the occurrence of common GI diseases until 2010, and data were analyzed using several different models. Generally speaking, the results showed that the risk of gastroesophageal reflux, intestinal obstruction or adhesions, and abdominal hernia was significantly higher in the PD group, whereas the risk of peptic ulcer disease and lower GI diverticula and bleeding was significantly greater in the HD group. Meanwhile, the risk of mesenteric ischemia, liver cirrhosis, and acute pancreatitis was higher in dialysis patients, but was not significantly different between the PD and HD groups; moreover, the risk of appendicitis in the PD group appeared to be lower than that in the HD group. In conclusion, dialysis patients have a higher risk of most common GI diseases, and PD and HD modalities are associated with different GI diseases.